Factors Explaining Procedural Pain Management in Newborn Intensive Care Unit: A Cross- Sectional Study - Tassaneeyarat, Sirinna; Deoisres, Wannee; Chaimongkol, Nujjaree (Celebes Nursing Journal, 2025)
Introduction: Recent research has highlighted the significant impact of procedural pain on critically ill neonates. However, effective pain management strategies to mitigate long-term negative consequences are still underutilized. Objective: To determine the effect of nurse factors on procedural pain management in neonates performed by neonatal nurses, when controlling organizational context factors and infant factors. Method: This study was cross-sectional correlation design. The participants consisted of 118 Thai NICU nurses. The Data collecting used by a self-report questionnaire. The descriptive statistics and hierarchical multiple regression analysis are used to analyze the data. Result: The findings showed that organizational supportive resources and nurse-physician collaboration had significantly positive effects on pain management in neonates (β = .349, p < .001, and β = .362, p < .001). Gestational age had a significant negative effect on pain management in neonates (β = -.414, p < .001). Knowledge, attitude, and nurses’ experience of infant care had significant positive effects on pain management in neonates (β = .435, p < .001, β = .257, p < .01, and β = .236, p < .01, respectively). When controlling for the organizational context factors and the infant factor, nurse factors still predicted procedural pain management in neonates. Together, the predictor variables explained 54.8% of the total variance of nurses’ pain management in neonates. It can conclude that nurse factors are important predictors of procedural pain management in neonates. Conclusion: Thus, there is a need for nurse empowerment and enhanced knowledge about neonatal pain assessment and management among NICU nurses.